Fully Bridged Triphenylamines Comprising Five- and Seven-Membered Rings - Michalsky, Ina; Gensch, Viktoria; Walla, Christian; Hoffmann, Marvin; Rominger, Frank; Oeser, Thomas; Tegeder, Petra; Dreuw, Andreas; Kivala, Milan (Chemistry - A European Journal, 2022)
A family of fully bridged triphenylamines with embedded 5- and 7-membered rings is presented. The compounds are potent electron donors capable to undergo donor/acceptor interactions with strong cyano-based acceptors both in the solid state and solution. These interactions were evaluated by IR and UV/vis spectroscopy as well as X-ray crystallography. The vinylene-bridged compound was oxidized to the corresponding 1,2-diketone which readily underwent acid-catalyzed condensation with selected 1,2-phenylenediamines. The resulting π-extended quinoxaline derivatives represent valuable building blocks for the development of functional chromophores upon appropriate functionalization.
CRIS-Team Scopus Importer:2022-05-20
Keywords: bridged triarylamines; charge transfer; co-crystallization; electron donor; N-heterocycle